2021
DOI: 10.1002/jcla.23719
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the platelet‐to‐lymphocyte ratio and diabetic foot ulcer in patients with type 2 diabetes mellitus

Abstract: Diabetic foot is a common and severe chronic diabetic complication and has become a public health issue, 1 with the global prevalence of diabetic foot ulcer (DFU) being 6.3%. 2 Around 25% of patients with diabetes develop a foot ulcer in their lifetime, 3 and compared to nondiabetic patients, those with DFU have higher amputation rates and increased mortality. 4 Peripheral arterial disease, diabetic peripheral neuropathy, deformity, previous amputation, and infection are the main factors contributing to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Biomarkers are valuable tools for these purposes. To date, multiple biomarkers focused on stratifying the risk of developing DFU have been studied, such as creatinine, lipid profile, apolipoproteins, hemoglobin A1c, platelet-to-lymphocyte ratio, and others [ 11 , 12 ]. The lipid profile and apolipoproteins have been associated with complications in cardiovascular and neuropathic diseases, the same ones associated with the development of DFU; given this, several studies have evaluated their association [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers are valuable tools for these purposes. To date, multiple biomarkers focused on stratifying the risk of developing DFU have been studied, such as creatinine, lipid profile, apolipoproteins, hemoglobin A1c, platelet-to-lymphocyte ratio, and others [ 11 , 12 ]. The lipid profile and apolipoproteins have been associated with complications in cardiovascular and neuropathic diseases, the same ones associated with the development of DFU; given this, several studies have evaluated their association [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 Similarly, Yue et al found that PLR was significantly increased during the onset of diabetic retinopathy (DR), 28 while Zhang et al reported that the PLR for patients with diabetic foot ulcers (DFU) increased significantly and was positively correlated with Wagner DFU grade. 29 As a potential biomarker reflecting inflammation responses, many studies have reported that PLR is positively correlated with traditional inflammatory markers. Since PLR is calculated as the ratio of platelets to lymphocytes, a high PLR can either occur as a result of the platelet count being high or the lymphocyte count being low.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Similarly, Yue et al found that PLR was significantly increased during the onset of diabetic retinopathy (DR), 28 while Zhang et al reported that the PLR for patients with diabetic foot ulcers (DFU) increased significantly and was positively correlated with Wagner DFU grade. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies researched the predictive value of both ratios for the occurrence of diabetic foot complications such as osteomyelitis, amputation, re-amputation and mortality. [22][23][24] Other authors used the P/L ratio to highlight the inflammatory state induced by the presence of DFU compared to those without, 25,26 or their predictive value for diabetic wound healing. 27 Yapici et al compared N/L ratio between three groups of patients with DFI who were treated either with antibiotics alone, debridement or amputation; however, and unlike our series, each group included a number of patients with osteomyelitis.…”
Section: Nl Lm and Pl Ratios Outcomesmentioning
confidence: 99%